Military assistance to the civil authority: medical liaison with the Manchester clinicians after the Arena bombing. Issue 2 (16th July 2018) - Bowley, Douglas M; Davis, N; Ballard, M; Orr, L; Eddleston, J
Abstract : UK Defence Medical Services' personnel have experienced an intense exposure to patients injured during war over the last decade and a half. As some bitter lessons of war surgery were relearned and innovative practices introduced, outcomes for patients impr oved consistently as experience accumulated. The repository of many of the enduring lessons learnt at the Role 4 echelon of care remain at the Queen Elizabeth Hospital Birmingham (QEHB), with the National Health Service and Defence Medical Services personnel who treated the returning casualties. On 22 May 2017, a terrorist detonated an improvised explosive device at the Manchester Arena, killing 22 and wounding 159 people. In the aftermath of the event, QEHB was requested to provide support to the Manchester clinicians and teleconferencing and then two clinical visits were arranged. This short report describes the nature of the visits, outlines the principles of Military Aid to the Civil Authority and looks to the future role of the Defence Medical Services in planning and response to UK terrorism events.